Pramod Bhatta, PhD (ed.): Education in Nepal, Problems Reforms and Social Change - Parajulie, Sachit (Himalayan Journal of Sociology and Anthropology, 2011)
Pramod Bhatta, PhD (ed.). Education in Nepal, Problems Reforms and Social Change, Published by: Martin Chautari, Chautari Book Series-55, (2009). Page: 373, ISBN: 978-9937-8194-0-4, Price: NRs 400 DOI: http://dx.doi.org/10.3126/hjsa.v4i0.4682 Himalayan Journal of Sociology and Anthropology Vol.IV (2010) 263-265